Footsteps on the sacred earth : Southwestern Collection of the Bata Shoe Museum - Oakes, Jill E. 1952-; Riewe, Roderick R., 1942- (printed for The Bata Shoe Museum by University of Toronto Press, 1999)
"Material and spiritual cultures of the indigenous peoples of the Southwest: Anasazi, Pueblo, Navajo, Apache, Kiowa and Comanche"--Resumé vydavatele
Keywords: obuv -- Spojené státy americké (jihozápadní oblast); Indiáni Severní Ameriky -- tradiční oděvy; Indiáni Severní Ameriky -- obuv; Indiáni Severní Ameriky -- dějiny; footwear -- United States, Southwestern; Indians of North America -- traditional dress; Indians of North America -- footwear; Indians of North America -- history; studie; studies